Global Health Collaboration Challenges and Lessons (SpringerBriefs in Public Health,, 2018)
This stimulating open access volume details the innovative work of the Pan Institution Network for Global Health in creating collaborative research-based answers to large-scale health issues. Equitable partnerships among member universities representing North America, Africa, Asia, and Europe reverse standard cross-national dynamics to develop locally relevant responses to health challenges as well as their underlying disparities. Case studies focusing on multiple morbidities and effects of urbanization on health illustrate open dialogue in addressing HIV, maternal/child health, diabetes, and other major concerns. These instructive examples model collaborations between global North and South as meaningful steps toward the emerging global future of public health. Included in the coverage: Building sustainable networks: introducing the Pan Institution Network for Global Health Fostering dialogues in global health education: a graduate and undergraduate approach Provider workload and multiple morbidities in the Caribbean and South Africa Project Redemption: conducting research with informal workers in New York City Partnership and collaboration in global health: valuing reciprocity Global Health Collaboration will interest faculty working within the field of global health; scholars within public health, health policy, and cognate disciplines; as well as administrators looking to develop international university partnerships around global health and graduate students in the areas of global health, health administration, and public health and related social sciences (e.g., sociology, anthropology, demography).